Isolation and Identification Endophytic Fungi of Peel of White Pomegranate (Punica granatum L.) - Nurul Husna; samingan samingan; iswadi iswadi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
ABSTRACTVascular plants have contain some microbes, one of them is endophytic fungi. Endophytic fungi is microorganisms present in the plant organs such as seeds, leaves, flowers, twigs, stems and roots. White pomegranate is one of vascular plants associated with endophytic fungi. White pomegranate contains many benefits in it, among others, as an antimicrobial. Endophytic fungi present in plant tissue to produce the same compound with host. The aim of the study is to determine the type of endophytic fungi in the peel of pomegranate and know the different types of endophytic fungi on three levels of fruit maturity The study conducted in February until May 2016 in biology Laboratory of educational Faculty, Syiah Kuala University. The approach that is used in this study is a qualitative approach with descriptive type. The data collection is conducted by several stages of sampling, media preparation, isolation of fungi and fungal identification. Based on the analysis of data, result of the study are: endophytic fungus found in the peel of pomegranate divided into seven types of fungi, they are Penicillium sp.1, Penicillium sp.2, Aspergillus sp.1, Aspergillus sp.2, Aspergillus sp.3, Phytium sp, and fungi can not be identified. There are different types of endophytic fungi on three levels of maturity of pomegranate are young, middle-aged and elderly, but there was one type of fungus that was on the third level of maturity pomegranate is Penicillium sp.1Key words: endophytic fungi, peel of white pomegranate, identification